Adaptive Leadership and Organizational Response Capacity to Contemporary Social Dynamics - Irfan, Mochamad; Hartono, Rudi (Journal of Social Science Studies, 2025)
This study explores how perceptions of adaptive leadership influence organizational responses to dynamic social issues through a qualitative literature review approach. The growing complexity of social expectations and stakeholder demands requires leaders to develop responsive capacities that go beyond conventional management practices. By synthesizing theoretical frameworks and empirical findings from diverse scholarly sources, this analysis examines cognitive mechanisms underlying leader interpretation of social signals and translation into organizational action. Findings reveal that adaptive leadership perception encompasses cognitive differentiation of social issues, emotional regulation, and capacity for systemic learning. Leaders with well-developed adaptive perceptions demonstrate greater ability to navigate value conflicts and engage stakeholders in collective problem-solving processes. Organizational responsiveness emerges from interactions between leadership perception, structural flexibility, and supportive cultural conditions that enable distributed leadership across organizational levels. This conceptual framework provides foundations for developing leadership programs that cultivate adaptive capacities aligned with contemporary social challenges. The study contributes to theoretical advancement in leadership studies and offers practical guidance for organizations seeking to enhance social responsiveness while maintaining operational effectiveness.